HEALTH CARE SPACES: GENERATORS OF WRITTEN CULTURE PRACTICES - Pamela Ayelen Sanchez (Universidad Nacional del Nordeste, 2019)
This article discusses the written cultural practices carried out by women in a hospital, a pharmacy and their homes, located in a mountainous city a few kilometers away from the city of Cordoba. The main lines of the same, is recovered from the Final Project of Bachelor "Practices of written culture of women of low schooling in spaces of health care and family support", completed in 2018. In order to recover the practices of written culture in the spaces mentioned above, based on in-depth interviews with three women attending adult primary school and observations in the city's Municipal Hospital and a pharmacy, the first step is to describe and analyse the written materials available in the above-mentioned spaces and in the interviewees' homes. Secondly, the practices of reading and writing that are carried out in these spaces, recovering: what, how, with whom and for what purpose they are read and written. Thirdly, the health care provided by one of the women interviewed, in order to stress some beliefs about the scarce knowledge and controls of people with low schooling regarding their health.